2021
DOI: 10.1029/2020jb021393
|View full text |Cite
|
Sign up to set email alerts
|

Geological Records of Coseismic Shear Localization Along the Yangsan Fault, Korea

Abstract: In natural fault zones, shear strain is mainly accommodated in fault rocks (or fault materials) that make up the fault core (i.e., a central high-strain zone of a brittle fault; Fossen, 2016). The shear strain may be localized in short-term and long-term scales. The long-term localization has been reported from both seismogenic and aseismic fault zones (e.g., Sibson, 2003). Seismic rupture events may repeatedly occur in a slip zone over a long period, expressed by progressive displacement of geomorphic feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…Gu et al. (2021) suggested that the structural maturity of the fault appears to fit the intermediate class (Class 2) following the criteria of Manighetti et al. (2007) based on the minimum values of fault length on land (∼200 km), fault initiation age (>70 Ma), maximum long‐term slip rate (∼0.4 cm/yr), and finite dextral offset (>20–30 km).…”
Section: The Yangsan Faultmentioning
confidence: 99%
See 2 more Smart Citations
“…Gu et al. (2021) suggested that the structural maturity of the fault appears to fit the intermediate class (Class 2) following the criteria of Manighetti et al. (2007) based on the minimum values of fault length on land (∼200 km), fault initiation age (>70 Ma), maximum long‐term slip rate (∼0.4 cm/yr), and finite dextral offset (>20–30 km).…”
Section: The Yangsan Faultmentioning
confidence: 99%
“…Recently, based on a compilation of previous results, Cheon et al (2019) proposed the tectonic evolution of the fault and age constraints, including the following: (a) Late Cretaceous sinistral movement with a component of extensional deformation (e.g., NW-SE-striking extensional structures, and the Dadaepo pull-apart basin between the Yangsan and Dongnae faults; Cheon et al, 2017;Cho et al, 2007Cho et al, , 2016Ha et al, 2016); (2) late Paleogene (∼43-23 Ma) dextral movement, which was the most intense phase of deformation on the fault, with 20-30 km of dextral offset being inferred from the distribution of several piercing points, such as A-type granite bodies (see Figure 1c; Chang et al, 1990;Hwang, Lee, et al, 2007;; and (c) subsequent reactivations along some segments during the late Miocene associated with sinistral kinematics (Chang, 2002;Chang & Chang, 1998;Choi et al, 2009). Gu et al (2021) suggested that the structural maturity of the fault appears to fit the intermediate class (Class 2) following the criteria of Manighetti et al (2007) based on the minimum values of fault length on land (∼200 km), fault initiation age (>70 Ma), maximum long-term slip rate (∼0.4 cm/yr), and finite dextral offset (>20-30 km).…”
Section: Early Faultingmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, primary on-fault paleoseismic features along the fault—such as surface faulting-induced sedimentation (e.g., fissure fill and colluvial wedge) and faulted and folded stratigraphic units—indicate seismic slip, because creep, slow slip, or small slip during small to moderate earthquakes generally leave no such signs of observable deformation 17 . In addition, recently reported microscopic features in the PSZ of the Yangsan Fault, such as narrow (a few millimeters) micro-slip zones, sharp surfaces, ultrafine (less than a few micrometers) materials, gouge injections, cortex structures, and spalling fractures of clasts, strongly support the occurrence of rapid seismic slip reaching the surface 25 , 28 , 35 , 45 . Therefore, the thin and straight slip zones that are located mostly along the boundary of the wide inherited weak zone have acted as conduits for repeated earthquake rupture propagations and could also be pathways for future rupture propagation when large slip is initiated along this fault at seismogenic depths 35 .…”
Section: Resultsmentioning
confidence: 80%
“…白水, 1988;Mänttäri et al, 2007) Ga,Sr,Ca が検出された (Fig. 15c) 3) や神城断層 の副次断層でも報告されている (Noda and Shimamoto, 2005;Boullier et al, 2009;Schuck et al, 2018;Komura et al, 2019;Gu et al, 2020;相山ほか, でも報告されている (重富・林, 1999;Otsuki et al, 2003;Noda and Shimamoto, 2005;Boullier et al, 2009;Chen et al, 2013;加藤ほか, 2015;相山ほか, 2017;Schuck et al, 2018;Komura et al, 2019;Gu et al, and Sasaki, T., 2017, Consideration of the activity of a fault based on detailed structural analysis of a fault fracture zone: Case study of the Yamada fault, western Japan. J. Japan Soc.…”
unclassified